Pulling The Strings Of Student Shoppers: How Service Quality, Pricing Power, And Promotional Strategy Shape Bukalapak’s Appeal Among Unri Management Undergraduates - Suhatman, Rido; Wasnury, Rendra; Siregar, Prima Andreas (JURNAL MANAJEMEN DAN BISNIS, 2025)
The rapid growth of the e-commerce industry in Indonesia has driven competition between digital platforms, including Bukalapak, which, despite having competitive service features, has not shown dominance in the preferences of young consumers. This study aims to analyze the effect of service quality, price, and promotion on the purchasing decisions of Bukalapak application users among students majoring in Management at University of Riau class of 2020. Using a quantitative approach with a case study strategy, data were collected through questionnaires and interviews and analyzed using multiple linear regression with the help of SPSS software. The results showed that promotion had the most significant influence on purchasing decisions, followed by service quality, whereas price had no significant effect. The findings confirm that the effectiveness of promotional communications and improvement of the quality of the digital service experience are the main factors influencing the purchasing behavior of the younger generation, while price considerations are no longer the dominant factor. The contribution of this research lies in a more contextualized understanding of e-commerce user preferences among university students, as well as enriching the digital marketing literature by highlighting the importance of marketing mix strategies based on specific user segments. The practical implications of the findings are aimed at local e-commerce platform managers to strengthen service aspects and adopt more adaptive promotional strategies in the face of competitive digital market dynamics.